2020
DOI: 10.3389/fncir.2019.00081
|View full text |Cite|
|
Sign up to set email alerts
|

Inhibitory Network Bistability Explains Increased Interneuronal Activity Prior to Seizure Onset

Abstract: Recent experimental literature has revealed that GABAergic interneurons exhibit increased activity prior to seizure onset, alongside additional evidence that such activity is synchronous and may arise abruptly. These findings have led some to hypothesize that this interneuronal activity may serve a causal role in driving the sudden change in brain activity that heralds seizure onset. However, the mechanisms predisposing an inhibitory network toward increased activity, specifically prior to ictogenesis, without… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 85 publications
(177 reference statements)
3
26
0
Order By: Relevance
“…In addition, baseline GABA decreased almost two minutes prior to the seizure, which was expected 46 , 72 . Furthermore, GABA and GLU increased just before the seizure, as others have shown 71 . GABA remained lower than baseline, as expected 47 , which likely contributed to the high E/I ratio.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…In addition, baseline GABA decreased almost two minutes prior to the seizure, which was expected 46 , 72 . Furthermore, GABA and GLU increased just before the seizure, as others have shown 71 . GABA remained lower than baseline, as expected 47 , which likely contributed to the high E/I ratio.…”
Section: Discussionsupporting
confidence: 53%
“…The concurrent and sudden decrease in GABA and GLU with a rapid rebound to baseline of the interictal-like spikes warrants further study 59,60 . It is commonly reported that neurons fire in abnormal levels of synchrony during a seizure 71 . We also noticed that large fluctuations in concentration occurred at the same time, starting with interictal spiking and continued through the seizure even though the baseline levels of the two neurotransmitters changed independently from each other.…”
Section: Uses Of Stimulation To Treat Neurological Disordersmentioning
confidence: 99%
“…We provide mathematical evidence for the viability of this mechanism and show that extrinsic stimulation can be tuned to optimize this stabilizing effect. We note that a similar dynamic, a bistability in a purely inhibitory network, provides a mechanism underlying the increased interneuronal activity observed immediately prior to seizure onset in recent work 45 . Viewed together with this previous work, our results support a general hypothesis that stabilization of neural network dynamics away from sudden state transitions reduce their susceptibility to dynamics associated with the transition into seizure.…”
Section: Introductionmentioning
confidence: 58%
“…More importantly in the context of this study, and the mathematical exploration of this phenomenon, is that such behaviour is a signature of multi-stability: the existence of multiple stable solutions to a dynamical system. Indeed, such multi-stability represents a key feature of potential seizure-inducing mechanisms, often represented by a sudden transition into some form of oscillatory dynamics, both in vivo and in silico 45 , 55 , 62 , 77 , 78 . Both excitatory and inhibitory cells fire synchronously following the transition into oscillatory dynamics in our spiking networks (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, of interest is the relationship between h-channels, PIR, and epilepsy. Recent experimental (Chang et al, 2018) and computational (Rich et al, 2020) support has been presented for a novel hypothesis of seizure initiation, termed the “GABAergic initiation hypothesis”, which posits that excessive inhibitory signalling may trigger seizure via a cascade of events including PIR spiking in pyramidal cells. The experimental work of Chameh et al (2019) reveals that human cortical L5 pyramidal cells can exhibit PIR spiking under current-clamp conditions, likely driven by the dynamics of the h-channel.…”
Section: Discussionmentioning
confidence: 99%